Highly selective cesium removal under acidic and alkaline conditions using a novel potassium aluminum thiostannate. (August 2022) - Yang, Chenyang; Suh, Yong Jae; Cho, Kuk
Abstract: The pH values of nuclear wastewater are extremely low or high, which make the efficient removal of 137 Cs a major concern among the issues for safety management and environmental remediation. Existing metal sulfides for Cs +  adsorption have shown poor performance at acidic and alkaline conditions, and the reason has not been revealed yet. Herein, a novel potassium aluminum thiostannate (KAlSnS-3) adsorbent was designed and its Cs +  adsorption mechanism over a wide pH range was investigated. We hypothesized that Al 3+ dopant on Sn 4+ sites would allow stable adsorption for Cs + upon its partial release at acidic and alkaline conditions. As a result, KAlSnS-3 demonstrated excellent adsorption performance across a broad pH range (1–13), and high selectivity toward Cs +, even under high salinity conditions (in tap water K d  = 3.12 × 10 4  mL/g; and in artificial seawater K d  = 3.42 × 10 3  mL/g). KAlSnS-3 also exhibited rapid adsorption kinetics ( R  = 97.6% in the first minute), a remarkable adsorption capacity (259.31 mg/g), and a high distribution coefficient (2.09 × 10 5  mL/g) toward Cs + . In addition, the high reusability of KAlSnS-3 was observed, suggesting its potential for real-world applications. The mechanism for enhancing performance at low and high pH values was discussed with the evidence of crystallinity, elemental concentrations, and binding energy of electrons based on the concept of electrostatic interactions and chemical affinity. In summary, this work provides insights into the mechanism of Cs + removal under a wide pH range, and the impressive Cs + adsorption performance indicates the application potential of KAlSnS-3 in wastewater treatment. Graphical abstract: Image 1 Highlights: A novel KAlSnS-3 adsorbent was designed and applied for cesium removal. Al 3+ release contributed to the good adsorption performance of Cs  +  at pH 2 and 12. The stable SnS2 -type crystal showed efficient adsorption of Cs + in a wide pH range. The rapid kinetics led to 97.6% removal of Cs + in the first minute. KAlSnS-3 maintained high selectivity toward Cs + even under high salinity conditions.